Legal positivism as a guarantee of ensuring human rights: philosophical-legal and historical-political dimensions - Podkovenko, Tetyana; Romaniv, Arsen (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article considered the main statements of legal positivism and the concept of human rights from the point of view of this type of legal understanding. The inclination of the libertarian-legal type of legal understanding to the «soft» version of legal positivism is highlighted. It is noted that modern Ukrainian jurisprudence has distorted the understanding of legal positivism in the direction of its extreme form – legalism. It has been analyzed that the Constitution of Ukraine, like the state, is willing to combine positivist and jusnaturalist approaches to legal understanding in the formation of legislation, but preference is given to legal positivism, in particular, in the field of constitutional justice. The propensity of political ideologies to choose one of the types of legal understanding in the formation of legislation has been revealed, depending on the point of view regarding the role and power of the state, but there is no clear answer regarding conservatism, so in this case it depends on the historical development of ideology (American and European model). Historical examples of the influence of legal positivism on the legal policy of states ruled by conservatives (Ukrainian State of Hetman Pavlo Skoropadskyi and Portugal under the rule of Antonio de Oliveira Salazar) are analyzed. In particular, the role of strong power and technical-legal tools in the protection of property rights («soft» positivism) is shown on the example of the Ukrainian State. Analyzing the policy of luso-tropicalism shows its dual nature – ensuring the equality of citizens and restraining decolonization processes in Portugal. In addition, luso-tropicalism became part of the policy of the right-wing conservative authoritarian regime of Salazar, while the guarantee of other important rights was ignored.